2018
DOI: 10.3847/1538-4357/aac264
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on Cosmological Parameters from the Angular Power Spectrum of a Combined 2500 deg2 SPT-SZ and Planck Gravitational Lensing Map

Abstract: We report constraints on cosmological parameters from the angular power spectrum of a cosmic microwave background (CMB) gravitational lensing potential map created using temperature data from 2500 deg 2 of South Pole Telescope (SPT) data supplemented with data from Planckin the same sky region, with the statistical power in the combined map primarily from the SPT data. We fit the lensing power spectrum to a model including cold dark matter and a cosmological constant (LCDM), and to models with single-paramet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 41 publications
10
38
0
Order By: Relevance
“…For comparison, in Fig. 2 we also show the constraints obtained by Simard et al (2018) with the CMB lensing band powers from 2500 deg 2 observed by SPT-SZ + Planck (Omori et al 2017), which are again consistent with the SPTpol ones and similar in extent.…”
Section: Constraints From Cmb Lensing Alonesupporting
confidence: 80%
See 4 more Smart Citations
“…For comparison, in Fig. 2 we also show the constraints obtained by Simard et al (2018) with the CMB lensing band powers from 2500 deg 2 observed by SPT-SZ + Planck (Omori et al 2017), which are again consistent with the SPTpol ones and similar in extent.…”
Section: Constraints From Cmb Lensing Alonesupporting
confidence: 80%
“…When the peak smearing information has been marginalized over, the amplitude of the lensing trispectrum relative to the best-fit ΛCDM parameters is consistent with expectations independent of the dataset combination. The results based on the SPT-SZ + Planck lensing map from Omori et al (2017) presented in Simard et al (2018) are also consistent with the SPTpol constraints.…”
Section: Lensing Amplitudessupporting
confidence: 80%
See 3 more Smart Citations